Studi Eksperimental Tentang Kondisi Ekstrem Pelat Beton Bersirip di Atas Tanah Pasir - Luckianto, Marvin; Vivi Bachtiar; M. Yusuf (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Roads are a crucial land transportation infrastructure that play an essential role in the distribution of goods and services. The existence of this infrastructure is vital for regional economic development. With the presence of roads, especially those prioritized for motor vehicles, travel time to destinations can be significantly reduced. The deflection of concrete pavement occurs due to loads acting on its surface. Therefore, the concrete slab or pavement must be designed with sufficient strength and an effective thickness. This study aims to analyze the effect of load position variation on the deflection of finned concrete slabs to determine the most critical (extreme) point. The research was conducted experimentally using an indirect loading method. The sample used was a finned concrete slab with a fin inclination of 30°, subjected to loading at the mid-point of the non-finned side, the mid-point of the finned side, and the corner of the finned concrete slab. Based on the loading test and graphical analysis, the slab loaded at the corner experienced the greatest deflection, indicating the most extreme condition, with a load of 14 kN producing a deformation of 17,719 mm.